The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1681/asn.2005090955
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitor or Angiotensin II Type 1 Receptor Antagonist Therapy Is Associated with Prolonged Patient and Graft Survival after Renal Transplantation

Abstract: Ten-year unadjusted functional graft survival rates were 76% among ACEI/ARB patients and 71% in noACEI/ARB recipients (P ‫؍‬ 0.57). In summary, the use of ACEI/ARB therapy was associated with longer patient and graft survival after renal transplantation. More frequent use of these medications may reduce the high incidence of death and renal allograft failure in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(145 citation statements)
references
References 33 publications
5
132
1
5
Order By: Relevance
“…Our findings are consistent with a recent report by Molnar et al (8), who, in a prospective cohort study, found that anemia at baseline significantly predicted mortality and graft failure over 4 yr follow-up and with two retrospective studies that demonstrated that PTA at 12 mo (defined as Hb Ͻ12 g/dl) was associated with decreased patient and graft survival (10) and that lower Hb was associated with adverse outcomes, including mortality and graft loss in renal tx patients (20).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with a recent report by Molnar et al (8), who, in a prospective cohort study, found that anemia at baseline significantly predicted mortality and graft failure over 4 yr follow-up and with two retrospective studies that demonstrated that PTA at 12 mo (defined as Hb Ͻ12 g/dl) was associated with decreased patient and graft survival (10) and that lower Hb was associated with adverse outcomes, including mortality and graft loss in renal tx patients (20).…”
Section: Discussionsupporting
confidence: 93%
“…A single-center retrospective study suggested that use of these agents was associated with improved allograft and patient survival but not deathcensored graft survival (24). A larger registry analysis concluded that the use of these agents had no benefit on either patient or graft survival (25).…”
Section: Hypertensionmentioning
confidence: 99%
“…In renal transplant recipients, microalbuminuria is a risk factor for graft loss and all-cause mortality (17). The effectiveness of RAS inhibitors for decreasing proteinuria following renal transplantation has been evaluated in various studies (16,(18)(19)(20). Heinze et al (18) demonstrated that treatment with ACEi and/or ARB led to a 45 and 43% reduction in the risk of graft loss and patient mortality, respectively.…”
Section: Discussionmentioning
confidence: 99%